Endogenous technical change, employment and distribution in the Goodwin model - Tavani, Daniele; Zamparelli, Luca (Düsseldorf, 2013)
"The Goodwin (1967) model of the growth cycle assigns distributional conflict a central role in the dynamics of capital accumulation, but is silent on the determinants of technical change. Following Shah and Desai (1981), previous studies focused on the effects of the direction, or bias of technical change on the growth cycle (van der Ploeg, 1987; Foley, 2003; Julius, 2005). Either implicitly or explicitly, these contributions adopted the induced innovation hypothesis by Kennedy (1964): there exists an innovation possibility frontier out of which profit-maximizing firms freely choose the optimal combination of capital- and labor-augmenting technical change, without having to allocate resources to R&D. Our focus is instead on the choice of intensity of technical change, that is the share of R&D expenditure in output. In our framework, innovation is a costly, forward-looking process financed out of profits, and pursued by owners of capital stock (capitalists) in order to foster labor productivity and save on labor requirements. Our main findings are: (i) similarly to the literature on the direction of technical change, an endogenous intensity of R&D ultimately dampens the distributive cycle; however, (ii) steady state per capita growth, income distribution and employment rate are endogenous, and depend on the capitalists' discount rate, the institutional variables regulating the labor market, and the size of subsidies to R&D activity. Implementing the model numerically, we show that: (iii) a reduction in the capitalists' discount rate lowers per-capita growth, the employment rate and the labor share; (iv) an increase in workers' bargaining power raises the labor share, while reducing employment and per-capita growth; (v) a balanced budget increase in the R&D subsidy also fosters per-capita growth, at the expenses of the labor share. The variations corresponding to (iv) and (v), however, can be small."